A Corporate Sustainable Responsibility Management Tool that Supports the Sustainable Development Goals - Nora Rodek; Zoltán Birkner; Tivadar Máhr; Tamás Rentz (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Nowadays, not only large companies are addressing the issue of sustainability, but the importance of the topic has also been widespread in politics, media and society. Attention is focused on climate change and thus on environmental issues, although sustainable development covers a wider topic area. As reflected in the United Nations' Sustainable Development Goals, it encompasses global issues, with priorities changing across countries and cultures. Each business, institution and municipality should support these goals to the best of its ability, following local characteristics and needs. Sustainable development deals with the causes and causes effects and the economic results derived from them in the context of global objectives, while the corporate sustainable responsibility (CSR) approach responds to the problems arising in the local space and the micro-environment of enterprises by involving their stakeholders. Small and medium-sized enterprises have a particularly important role to play in promoting CSR as they are connected with local communities, being aware of local characteristics and problems, and serving as an example and motivator to their stakeholders for responsible and sustainable operations, active social engagement and value creation. The purpose of this study is to show how our management tool (CSR EMAT) supports the implementation of Sustainable Development Goals.
Keywords: M14; 330; Corporate sustainable responsibility; sustainable development; Sustainable Development Goals; CSR EMAT